L-Tryptophan Mitigates Cannibalism and Improves Growth of Asian seabass, Lates calcarifer Reared in a RAS System - Md. Shahzad Kuli Khan; Krishna R. Salin; Amararatne Yakupitiyage; Takuji W. Tsusaka; Loc Thai Nguyen; Mohammad Abdul Momin Siddique (Aquaculture Journal, 2023)
Severe cannibalism can result in a significant loss of productivity during the nursery phase of Asian seabass, Lates calcarifer. The present study aimed to determine the effect of dietary tryptophan on growth, feed utilization, cannibalism, survival, and muscle proximate composition of Asian seabass juveniles (initial size, 2.77 ± 0.04 cm in length and 0.29 ± 0.01 g in weight) in a recirculating aquaculture system (RAS) at different stocking densities. The tryptophan levels were set at 0.41% (control diet, standard dosage for normal growth and survival of Asian seabass), 1.00% (Diet 1), and 1.50% (Diet 2), while the stocking densities were set at 0.5 ind./L and 1.5 ind./L. The results indicated that dietary supplementation with L-tryptophan (TRP) and fish stocking density had a significant effect on fish growth parameters, feed utilization, cannibalism, survival, and muscle lipid content (p < 0.05) over the 45-day trial. The maximum length, weight, WG, and SGR were 11.64 ± 0.35 cm, 22.93 ± 2.67 g, 22.64 ± 2.67 g, and 9.63 ± 0.27%, respectively, in the fish fed Diet 2, and 11.35 ± 0.22 cm, 24.38 ± 1.28 g, 24.09 ± 1.28 g, and 9.82 ± 0.11% at a 1.5 ind./L stocking density. The lower FCR (0.81 ± 0.04) and higher PER (2.98 ± 0.16) ensured better utilization of Diet 1 than the other diets. Moreover, significant interaction effects between diet and stocking density were observed in total yield, cannibalism, and survival of the Asian seabass. Significantly higher survival rates of 76.11 ± 3.90% in the Diet 1 group and 76.28 ± 2.88% in 0.5 ind./L stocking density were obtained, which is promising. The study concludes that dietary supplementation with 1.00% TRP was effective in reducing cannibalism and increasing the survival of the Asian seabass nursery reared in RAS at a lower stocking density (i.e., 0.5 ind./L), whereas 1.50% supplemental TRP at a higher stocking density (i.e., 1.5 ind./L) significantly increased the cannibalism and growth, which in turn reduced the survival rate.